SAUNA TRADISIONAL FINLANDIA DENGAN TINGKAT STRES PADA PRA LANSIA DAN LANSIA - Azizha Multhazam Sudding; Fransisca Chondro (Jurnal Akta Trimedika, 2024)
Stress is a person's reaction, both physically and emotionally, that happens when there are changes in the environment that needed adjustment from that person. All ages, including the elderly, can suffer from stress. Several methods can be used to reduce stress, one of which is using a sauna. This study aims to assess the relationship between the use of traditional Finnish saunas and stress levels in pre-elderly and elderly. This study used an observational analytic method using a cross-sectional design study. The number of subjects required in this study is 87 respondents. Sampling was taken by consecutive non-random sampling, and data were collected using questionnaire regarding characteristics of the respondents in the use of saunas and the Perceived Stress Scale (PSS-10) to measure the stress level. Bivariate analysis in this study is done using SPSS program with a significance level of p<0.05. Based on the results of the chi-square test it can be concluded that there was a statistically significant relationship between type of sauna and stress levels (p = 0.016), there was a statistically significant relationship between duration of sauna and stress level (p=0.01), and there was a statistically significant relationship between frequency of sauna usage and stress level (p = 0.015). Conclusion: There was a statistically significant relationship between the type of sauna, duration of sauna, and the frequency of sauna usage with stress levels in pre-elderly and elderly